2017
DOI: 10.1002/jbmr.3308
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Fiber Intake and Bone Loss in the Framingham Offspring Study

Abstract: Dietary fiber may increase calcium absorption, but its role in bone mineralization is unclear. Furthermore, the health effect of dietary fiber may be different between genders. We examined the association between dietary fiber (total fiber and fiber from cereal, fruits, vegetables, nuts and legumes) and bone loss at the femoral neck, trochanter and lumbar spine (L2–4) in older men and women. In the Framingham Offspring Study, at baseline (1996–2001), diet was assessed using the Willett food frequency questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
3
24
1
3
Order By: Relevance
“…A recently published 8-year of follow-up longitudinal cohort study using the Framingham offspring cohort demonstrated the higher the amount of daily dietary fiber the male participants consumed, the less bone loss of femur neck they experienced. [23] The positive relationship between fiber intake and bone health in younger male group in our cross-sectional study was in line with the study outcome of the Framingham offspring cohort study; higher fiber intake increased BMD of femur neck only in males. Notably, sex difference in the association of dietary fiber and BMD was evident in both studies regardless of types of dietary fiber that study participants consumed; most of the study participants in the Framingham offspring cohort study were Caucasians whose sources of fiber may be different than those of most Koreans.…”
Section: Discussionsupporting
confidence: 87%
“…A recently published 8-year of follow-up longitudinal cohort study using the Framingham offspring cohort demonstrated the higher the amount of daily dietary fiber the male participants consumed, the less bone loss of femur neck they experienced. [23] The positive relationship between fiber intake and bone health in younger male group in our cross-sectional study was in line with the study outcome of the Framingham offspring cohort study; higher fiber intake increased BMD of femur neck only in males. Notably, sex difference in the association of dietary fiber and BMD was evident in both studies regardless of types of dietary fiber that study participants consumed; most of the study participants in the Framingham offspring cohort study were Caucasians whose sources of fiber may be different than those of most Koreans.…”
Section: Discussionsupporting
confidence: 87%
“…Another possibility is that a positive effect of grape oligosaccharides and fiber on bone architecture was inhibited by co-ingestion of probiotics. Higher dietary and specifically fruit fiber intake has been shown to protect against femoral neck bone loss in men [ 88 ]. Mechanisms include improved mineral solubility and absorption resulting from growth of gut bacteria that ferment oligosaccharides and fiber to short-chain fatty acids [ 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant associations were found for young women or older men. A 2018 Framingham Offspring Study (792 men, mean age 58 years; 1065 women; mean age 57 years; 8 years follow-up) observed significantly reduced annualized loss of femoral neck bone mineral density (predictive of hip fracture risk) per 5 g/day total fiber by 0.06% or fruit fiber by 0.04% [344]. A 2017 Chinese cross-sectional study (3089 participants; age range 40 to 75 years; 66% women) observed that high fruit intake had dose-dependent associations with greater bone mineral density and a lower risk of osteoporosis; but this was not shown for vegetables [345].…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%